Medical tourism trends in Poland - Religioni, Urszula; Religioni, Mateusz (Medical and Biological Sciences, 2015)
The global increase in the flow of patients and health professionals as well as medical technology has led to new patterns of consumption and production of medical services in the past decades. Free movement of goods and services contributed to the liberalization of trade in health services. Medical tourism is one of the forms of health tourism, rapidly growing on the global market. In medical tourism, patients travel to neighboring or distant countries in order to receive medical assistance under the global trend of combining treatment with leisure. The development of medical tourism is also observed in Poland. Citizens of Germany, Great Britain and the Scandinavian countries use the services offered in Polish medical institutions most frequently. One of the main problems in the further development of Polish medical tourism is a lack of implementation of the European Directive on the application of patients' rights in cross-border healthcare. This article describes the process of medical tourism development in Poland. The phenomenon of medical tourism, types of health tourism and main drivers of that process are also characterized by the authors.